Similar Conditions With Opposite Effects: Predation‐Risk Effects on Prey Abundance Are Highly Contingent - Scott D. Peacor; Clayton E. Cressler; Kevin L. Pangle; Alexandra V. Rafalski; Chao Song; Earl E. Werner (Ecology and Evolution)
ABSTRACT Experiments have shown that predation‐risk effects on prey fitness can be highly contingent on environmental conditions, suggesting a potential difficulty in generalizing risk effects on prey abundance in natural settings. Rather than study the influence of a particular controlled factor, we examine the problem with a novel approach. We examined the influence of risk effects in multiple experiments performed under similar study conditions. Any differences in the experiments would typically be deemed incidental, that is, they would not be given attention in methodology, nor be presented as factors affecting results or inferences. Therefore, any differences in the magnitude and direction of risk effects among experiments would indicate that risk effects on prey population abundance are strongly influenced by context in natural communities. The multiple experiments were conducted under similar conditions, objectives, measurables and implementation, and captured much of the complexity of natural systems (e.g., they were performed with diverse prey assemblages (≥ 11 taxa) over multiple prey generations). Our results highlight the potentially profound context dependence of risk effects: risk effects on the density of some zooplankton species varied between a significant negative effect in one experiment to a significant positive effect in another, whereas other species showed significant negative or positive effects in one experiment and no effect in another. We review mechanisms that could underlie risk effects having opposite effects on the same prey. Our findings illustrate that risk effects observed in one study may not hold, even for the same species in the same system.